Man’s Dialogical Nature and the Dialogue of Religions - Chethimattam, John B (Journal of Dharma, 1999)
This can be called an era of dialogue. Scientific and technological progress has made our globe rather small and brought men closer together. Communications explosion has made our earth a global village where news even from the remotest comers are communicated all over the world via satellites in matter of seconds. In such a situation man cannot remain isolated from other men, nor hermetically insulated against their ideas and aspirations. The two great world wars accelerated the progress by throwing peoples for centuries kept apart by geography, religion and culture into the laps of each other during a catastrophic dislocation of normal living. Dialogue among Christian churches in the West started when Catholics were forced by circumstances to accommodate Protestant refugees in their churches and vice versa Protestant had to show hospitality to Catholic refugees. The long forgotten religions of the East came fully into the picture when nations of the East gained their political independence and asserted their identity in the world body of nations. But this spontaneously growing dialogue among religions only brings out a long neglected dimension of man; his dialogal physic structure, which contemporary philosophical thinking and religious experience have brought into focus.